Develop Community Action Plans for Meher 2014 - International Potato Center (International Food Policy Research Institute, 2014)
This data study contains data from participatory community analyses (PCA) in 8 kebeles in the Amhara, Tigray, Oromia and SNNPR regions. Project title: Develop community Action Plans for Meher 2014. Project abstract: In 2014, participatory community analyses (PCA) were undertaken by multi-disciplinary facilitation teams in 8 kebeles in the Amhara, Tigray, Oromia and SNNPR regions, producing a list of priority farming enterprises, their current bottlenecks, as well as farmer-perceived opportunities for improving income, food security and/or reducing overall risks by intensifying farm enterprises. The PCA was carried out in discussions with kebele members and local leaders, with over 250 men, women and young people. Feedback on the results will be given to the farmers and future participatory planning and implementation of activities based on the results of the PCA and feedback sessions. Project website: http://africa-rising.net